DAMPAK PANDEMI COVID-19 TERHADAP PERAN ORANG TUA DAN GURU DALAM MENINGKATKAN KUALITAS PEMBELAJARAN DARING ANAK USIA SEKOLAH DASAR - Puji Asmaul Chusna; Ana Dwi Muji Utami (PREMIERE : Journal of Islamic Elementary Education, 2020)
This research aims to know the impact of the covid-19 pandemic on parents and teachers in improving the quality of online learning for elementary school age children, to find out the obstacles and supporters faced by teachers and parents in improving the quality of online learning for elementary school age children. This research is a qualitative descriptive study. The object of this study were teachers, students' parents, and students in the shade of MI AL-HIKMAH Talun Blitar. Data collection techniques using observation and interviews. Semi-structured interviews were conducted with a list of interview questions to be developed with related literature. The results of this study show the results that teachers always provide motivation, provide customised tasks with abilities and never squeeze in every task. Provide full guidance if needed by parents. This is also done by parents of students actively accompanying and guiding them in working on assignments. Trying to be comfortable but still disciplined to the maximum in accordance with the teacher's instructions. However, in addition to the less supportive facilities and infrastructure, they complained about the additional cost of buying an internet quota, the signals that were less supportive, children at home quickly got bored and misused when using an Android cellphone.